The patterns of traditional healing practices among first-contact patients with psychiatric services in two mental health facilities in Jaffna - Mahendranathan, S.; Umahsuthan, V.; Ponnuraj, K.; Kamalnathan, P.; Sivayokan, S. (University of Jaffna, 2024)
Background and objectives: Mental illnesses remain a global health challenge, mandating prompt identification and intervention. Social stigma and ignorance often deter individuals from seeking timely care. Sufferers explore alternative explanations for the origin of mental illnesses, and most resort to traditional healing rituals that are deeply rooted in our culture and are perceived to provide holistic care. This study investigated the relationship between different mental illnesses and traditional healing practices utilised by first-contact patients presenting to the psychiatry units of Teaching Hospital Jaffna and Base Hospital Tellippalai. Methods: This institution-based descriptive cross-sectional study was conducted between October 2021 and April 2022, involving 353 participants. Data were collected through a semistructured, interviewer-administered questionnaire at inpatients and outpatient settings of the above-mentioned psychiatric facilities. Chi-square test was used to determine the significance. Results: The mean age of the sample was 33.1 (SD = 13.86) years with slight male preponderance and the majority were Tamil Hindus. Common mental illnesses were depressive disorder (24.4%), followed by mental and behavioral disorders due to substance use (20.7%) and adjustment disorder (12.2%). Over half the sample (57.5%) had sought one or more traditional healing rituals before coming into contact with psychiatric services. Having adjustment disorders was significantly associated with the practice of evicting the evil eye (p=0.021), while depression was associated with chanting religious slogans (p=0.01), and schizophrenia with tying of enchanted threads/talismans/amulets (p=0.044). Conclusion: Integrating scientifically validated elements of traditional healing into mental health treatment, while ensuring the duration of untreated illness is not extended, is crucial. Additional research is needed to comprehend the intricate relationships between traditional healing practices and mental illness as well as their impact on mental health care. Educating Research Conference of Faculty of Medicine, University of Jaffna – August 2024 traditional healers on recognizing major mental illnesses and working with them for timely referrals would be considered the way forward.
Keywords: Traditional healing rituals; Mental illness; First-contact patients to psychiatric services; Jaffna